Bidirectional charging as a strategy for rural PV integration in China - Anders Hove (The Oxford Institute for Energy Studies, 2023)
Bidirectional charging capabilities will soon be offered on more electric vehicle (EV) models, but the market appeal and economic potential of this technology are largely unknown and widely debated. China is the largest EV market, and is also in the midst of a major build-out of distributed rooftop PV. The recency of these two trends, combined with the imminent arrival of bidirectional charging on the market, make it timely to evaluate the potential of combining these three technologies: PV, heat pumps, and bidirectional charging as an energy storage solution to enable home electrification. This study extends an earlier analysis of rural PV and heat pumps to include an evaluation of the potential for bidirectional EV charging in these areas. Bidirectional charging could help resolve the problem of midday PV overproduction, providing stored energy for heating and cooling loads, without the excessive capital cost of a home battery system. However, this study shows that under current electricity rates, bidirectional charging for rural residents is presently uneconomical. While bidirectional charging increases household self-sufficiency and improves integration of midday solar output, more incentives and electricity price adjustments would be necessary to make it economically attractive.
Keywords: 330; bidirectional charging; China; Electricity; EV; heat-pumps; PV